How do you factor 20x^4+16x^3-5x-420x4+16x35x4?

1 Answer
Oct 2, 2016

20x^4+16x^3-5x-4 = (4x^3-1)(5x+4)20x4+16x35x4=(4x31)(5x+4)

color(white)(20x^4+16x^3-5x-4) = (root(3)(4)x-1)(2root(3)(2)x^2+root(3)(4)x+1)(5x+4)20x4+16x35x4=(34x1)(232x2+34x+1)(5x+4)

Explanation:

Notice that the ratio of the first and second terms is the same as that of the third and fourth terms. So this quadrinomial will factor by grouping:

20x^4+16x^3-5x-4 = (20x^4+16x^3)-(5x+4)20x4+16x35x4=(20x4+16x3)(5x+4)

color(white)(20x^4+16x^3-5x-4) = 4x^3(5x+4)-1(5x+4)20x4+16x35x4=4x3(5x+4)1(5x+4)

color(white)(20x^4+16x^3-5x-4) = (4x^3-1)(5x+4)20x4+16x35x4=(4x31)(5x+4)

We can factor 4x^3-14x31 as a difference of cubes using irrational coefficients:

a^3-b^3 = (a-b)(a^2+ab+b^2)a3b3=(ab)(a2+ab+b2)

So:

4x^3-1 = (root(3)(4)x)^3-1^34x31=(34x)313

color(white)(4x^3-1) = (root(3)(4)x-1)((root(3)(4)x)^2+root(3)(4)x+1)4x31=(34x1)((34x)2+34x+1)

color(white)(4x^3-1) = (root(3)(4)x-1)(root(3)(16)x^2+root(3)(4)x+1)4x31=(34x1)(316x2+34x+1)

color(white)(4x^3-1) = (root(3)(4)x-1)(2root(3)(2)x^2+root(3)(4)x+1)4x31=(34x1)(232x2+34x+1)